2017
DOI: 10.3389/fmicb.2017.01687
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Intensity Exercise Affects Gut Microbiome Composition and Influences Cardiac Function in Myocardial Infarction Mice

Abstract: Physical exercise is commonly regarded as protective against cardiovascular disease (CVD). Recent studies have reported that exercise alters the gut microbiota and that modification of the gut microbiota can influence cardiac function. Here, we focused on the relationships among exercise, the gut microbiota and cardiac function after myocardial infarction (MI). Four-week-old C57BL/6J mice were exercised on a treadmill for 4 weeks before undergoing left coronary artery ligation. Cardiac function was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 44 publications
7
74
1
5
Order By: Relevance
“…Along with improved cardiac function in myocardial infarction mice, Liu et al . (27) showed that exercise training increased biodiversity and the relative abundance of key taxa with health‐promoting metabolic activities, such as Butyricimonas, Prevotella, and Akkermansia. Other studies also showed that exercise training resulted in a significant decrease in the abundance of potentially pathogenic Bacteroidetes such as Bacteroides vulgatus (28) and increases in the abundance of anti‐inflammatory and antiobesity Verrucomicrobia, such as Akkermansia muciniphila (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with improved cardiac function in myocardial infarction mice, Liu et al . (27) showed that exercise training increased biodiversity and the relative abundance of key taxa with health‐promoting metabolic activities, such as Butyricimonas, Prevotella, and Akkermansia. Other studies also showed that exercise training resulted in a significant decrease in the abundance of potentially pathogenic Bacteroidetes such as Bacteroides vulgatus (28) and increases in the abundance of anti‐inflammatory and antiobesity Verrucomicrobia, such as Akkermansia muciniphila (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lambert et al (24) showed that 6 wk of low-intensity treadmill running resulted in lower abundances of Bacteroidetes genera (26) showed that running and wheeling exercise led to higher abundances of Firmicutes, Proteobacteria, and Actinobacteria phyla in fecal samples of mice. Along with improved cardiac function in myocardial infarction mice, Liu et al (27) showed that exercise training increased biodiversity and the relative abundance of key taxa with health-promoting metabolic activities, such as Butyricimonas, Prevotella, and Akkermansia. Other studies also showed that exercise training resulted in a significant decrease in the abundance of potentially pathogenic Bacteroidetes such as Bacteroides vulgatus (28) and increases in the abundance of anti-inflammatory and antiobesity Verrucomicrobia, such as Akkermansia muciniphila (29).…”
Section: Discussionmentioning
confidence: 99%
“…168 It has also been hypothesized that a higher training regime plus a higher intake of protein (as in many endurance athletes) may negatively influence the microbiota composition. 170 Other studies, however, found only moderate changes to gut microbiota composition and no significant changes reported in the inflammatory profile, after a moderate aerobic exercise intervention in mice. 169 In mice, there is a significant relationship between myocardial infarction and gut microbiota composition after physical exercise.…”
Section: Microbiotamentioning
confidence: 95%
“…Several studies suggest that exercise elevates the ratio of Firmicutes to Bacteroidetes (Petriz, et al , ; Lambert, et al , ) and increases the levels of the bacterial metabolite butyrate (Allen, et al , ). Alterations in the gut microbial structure induced by physical exercise are associated with the prevention of cardiac dysfunction in myocardial infarction mice (Liu, et al , ). Interestingly, LPS levels are elevated in CVD and some cardiometabolic disorders (Kallio, et al , ), and high‐endurance training can decrease plasma LPS levels (Lira, et al , ).…”
Section: Gut Microbiota Interventions For Cvdmentioning
confidence: 99%